Gluconolactone in Cosmetic (Review Article) - Titiek Indah Wulaningsih (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Hidroxy acid is one of the active substances that is widely used in the cosmetic field. Its use is very wide, but there are several classes of hydroxy acid that are irritative. The use of hydroxy acids can cause skin redness, itching, and tension in the skin. Other hydroxy acids are needed that can meet consumer needs without unwanted side effects. Method: This article uses research methods through literature search methods by collecting journals related to research objectives. Articles were found on Google Scholar's seaching engine as many as 27 articles. Objective: To determine the effectiveness of gluconolactone as a skin barrier, antiaging, and as an antiacne. Result and Discussion: The antioxidant effect of gluconolactone can also be used as a sunscreen by capturing free radicals formed when the skin is exposed to the sun. Conclusion: From the search it was found that gluconolacntone can act as a skin barrier protector, anti-acne as well as antianging